2018
DOI: 10.1186/s12991-018-0222-2
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of depression with comorbid substance use dependency in pregnant adolescents from an informal settlement of Nairobi: drawing implications for treatment and prevention work

Abstract: IntroductionAdolescent pregnancy is a highly prevalent and significant public health problem in Kenya, and mental health needs of pregnant adolescent girls have been overlooked. Nearly, 50% of the world’s population comprises children and adolescents and 85% live in lower and middle-income countries.ObjectivePregnant adolescents were interviewed to ascertain certain social determinants of mental health such as social support, partner or parent support, and demographic profile and assessed for depression using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
(47 reference statements)
2
27
0
Order By: Relevance
“…In the adjusted models, the Enter method was used, and all the predictors were entered into the models predicting each of depression, anxiety and suicidal behaviors, respectively. All the variables (confounding) controlled for in the adjusted models were based on their significant associations with mental health problems as reported in previous literature, e.g., [ 4 , 7 , 8 , 9 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In each adjusted model, the influence of a particular predictor was examined by controlling for all other predictors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the adjusted models, the Enter method was used, and all the predictors were entered into the models predicting each of depression, anxiety and suicidal behaviors, respectively. All the variables (confounding) controlled for in the adjusted models were based on their significant associations with mental health problems as reported in previous literature, e.g., [ 4 , 7 , 8 , 9 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In each adjusted model, the influence of a particular predictor was examined by controlling for all other predictors.…”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review, strong evidence of an association between poor sleep and perinatal depression was reported [ 25 ]. In a study among pregnant girls in Kenya, it was observed that substance use significantly was significantly associated with depression [ 26 ]. These findings have demonstrated the impact of psycho-behavioral factors on prenatal mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…For adolescents growing up in informal settlements, they also face additional challenges , including exposure to high violence , maltreatment experience during childhood , with an absence of male partners or family support , and engaging in risky early and unprotected sexual exposure [ 22 , 23 ]. Moreover, adolescent mothers in SSA tend to experience greater barriers and stigma in navigating health services , being taken seriously by the health workers and relatives, which further exacerbates their stress and negative parenthood experience [ 24 27 ]. These cumulative stressors experienced during adolescent motherhood aggravates parenting stress [ 28 ] and increase the risk for depression [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from South Africa, Uganda and Kenya show that age-specific risk factors include poverty, lower socio-economic status, lack of social capital and support, substance use and exposure to violence and traumatic events[710]. Comorbid substance use and mental health disorders are also common, creating a double burden [11][12]. Some of the protective factors for mental health disorders in sub-Saharan Africa include good parenting and social support [13,14].…”
Section: Introductionmentioning
confidence: 99%